2016
DOI: 10.1590/1413-70542016402043315
|View full text |Cite
|
Sign up to set email alerts
|

Neutral detergent fibre in piglet diets: performance and gastrointestinal implications

Abstract: The intestinal health of piglets depends on the balance between diet, microflora and mucosal integrity. Disruption of this balance can compromise the digestive functions, leading to diarrhoeal frame and decline in performance of piglets. However, the level and type of fibre can limit digestive disorders. Thirty newly weaned piglets were used to evaluate the levels of neutral detergent fibre (NDF) in diets regarding performance, pH, viscosity and concentration of short chain fatty acids of digestive contents, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…The strongest correlations (greater than 0.600; P < 0.01) were observed between feed conversion and inclusion of fibrous ingredient and with the consumption of fibers in feed. NEPOMUCENO et al (2016) reported that higher levels of NDF in the diet directly affect the performance of pigs, since they negatively affect digestibility and thus the energy intake of animals to Table 4 -Correlations of the dietary fiber content with the performance responses and carcass characteristics of finishing pigs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The strongest correlations (greater than 0.600; P < 0.01) were observed between feed conversion and inclusion of fibrous ingredient and with the consumption of fibers in feed. NEPOMUCENO et al (2016) reported that higher levels of NDF in the diet directly affect the performance of pigs, since they negatively affect digestibility and thus the energy intake of animals to Table 4 -Correlations of the dietary fiber content with the performance responses and carcass characteristics of finishing pigs.…”
Section: Resultsmentioning
confidence: 99%
“…ANIMAL PRODUCTION of crude fiber, neutral detergent fiber and acid detergent fiber. The methods used to measure the fibrous fractions of foods are correlated to simulate enzymatic digestion, but with difficult practical application (NEPOMUCENO et al, 2016) and or have limitations such as crude fiber. The method proposed by Van Soest (1967) determines the fractions of neutral detergent fiber (Hemicellulose and cellulose) and acid detergent fiber (cellulose) insoluble fractions (PASCOAL & WATANABE, 2014;NEPUCENO et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the content of less-fermentable fiber is associated with a reduction in E. coli count in the feces [36]. In a recent study, Nepomuceno et al observed a linear decrease in the occurrence of diarrhea when NDF content was increased from 8.5 to16.5% [37]. Hence, in addition to the hydrolysable tannins, the 2% unit greater NDF content in the diet containing CE could have partially helped in reducing both ETEC shedding and the occurrence of diarrhea.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the content of less-fermentable fiber is associated with a reduction in E. coli count in the feces [37]. In a recent study, Nepomuceno et al observed a linear decrease in the occurrence of diarrhea when NDF content was increased from 8.5 to 16.5% [38]. Hence, in addition to the hydrolysable tannins, the 2% unit greater NDF content in the diet containing CE could have partially helped in reducing both ETEC shedding and the occurrence of diarrhea.…”
Section: Effects Of Chestnut Extract Supplementationmentioning
confidence: 98%